2018
DOI: 10.3389/fimmu.2018.02675
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 5 Deficiency Does Not Compromise Innate Immune Responses to Bacterial Infections

Abstract: Sirtuin 5 (SIRT5) is a member of the family of NAD+-dependent lysine/histone deacetylases. SIRT5 resides mainly in the mitochondria where it catalyzes deacetylation, demalonylation, desuccinylation, and deglutarylation of lysine to regulate metabolic and oxidative stress response pathways. Pharmacologic inhibitors of SIRT5 are under development for oncologic conditions, but nothing is known about the impact of SIRT5 on antimicrobial innate immune defenses. Using SIRT5 knockout mice, we show that SIRT5 deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
0
25
1
Order By: Relevance
“…The extracellular acidification rate (ECAR), a readout of the glycolytic activity, was not affected in resting and LPS stimulated SIRT3/5 −/− BMDMs (Figure 1I and Supplementary Figure S3A). OCR and ECAR were similarly affected in resting SIRT3 −/− BMDMs (Supplementary Figure S3B) and SIRT5 −/− BMDMs (38). The dependency, capacity, and flexibility of BMDMs to oxidize the mitochondrial fuels glucose, glutamine and fatty acids were identical for SIRT3/5 +/+ and SIRT3/5 −/− BMDMs (Figure 1J).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The extracellular acidification rate (ECAR), a readout of the glycolytic activity, was not affected in resting and LPS stimulated SIRT3/5 −/− BMDMs (Figure 1I and Supplementary Figure S3A). OCR and ECAR were similarly affected in resting SIRT3 −/− BMDMs (Supplementary Figure S3B) and SIRT5 −/− BMDMs (38). The dependency, capacity, and flexibility of BMDMs to oxidize the mitochondrial fuels glucose, glutamine and fatty acids were identical for SIRT3/5 +/+ and SIRT3/5 −/− BMDMs (Figure 1J).…”
Section: Resultsmentioning
confidence: 90%
“…Macrophages and neutrophils are proficient at sensing microbial products and play key defense roles during infections. SIRT3 and SIRT5 single deficiency did not influence antimicrobial host defenses (37, 38). Therefore, we asked whether dual deficiency of SIRT3 and SIRT5 would reveal a phenotype unseen in single knockouts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Whether the enzyme responsible for succinylation existed is still debatable, but SIRT5 has been identified as an important desuccinylase, which plays pivotal functions in diverse pathways (Park et al, 2013;Rardin et al, 2013;Anderson et al, 2014;Wang et al, 2017a;Heinonen et al, 2018). However, to date, the connection between protein desuccinylation catalyzed by SIRT5 and RLR-mediated innate immune activation has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate that Heinon et al have recently reported that Sirt5 deficiency does not compromise the response to bacterial infection (Heinonen et al, 2018). We used different background mice and bacterial strains from them.…”
Section: Cellmentioning
confidence: 99%